Beispiel Nr: 01
$ \text{Gegeben:}\\\text{Höhe} \qquad c \qquad [m] \\ \text{Breite} \qquad b \qquad [m] \\ \text{Oberfläche} \qquad O \qquad [m^{2}] \\ \\ \text{Gesucht:} \\\text{Länge} \qquad a \qquad [m] \\ \\ a = \frac{O-2\cdot b\cdot c}{2\cdot (b+c)}\\ \textbf{Gegeben:} \\ c=2m \qquad b=7m \qquad O=2m^{2} \qquad \\ \\ \textbf{Rechnung:} \\ a = \frac{O-2\cdot b\cdot c}{2\cdot (b+c)} \\ c=2m\\ b=7m\\ O=2m^{2}\\ a = \frac{2m^{2}-2\cdot 7m\cdot 2m}{2\cdot (7m+2m)}\\\\a=-1\frac{4}{9}m \\ \small \begin{array}{|l|} \hline c=\\ \hline 2 m \\ \hline 20 dm \\ \hline 200 cm \\ \hline 2\cdot 10^{3} mm \\ \hline 2\cdot 10^{6} \mu m \\ \hline 0,002 km \\ \hline \end{array}\\ \small \begin{array}{|l|} \hline b=\\ \hline 7 m \\ \hline 70 dm \\ \hline 700 cm \\ \hline 7\cdot 10^{3} mm \\ \hline 7\cdot 10^{6} \mu m \\ \hline 0,007 km \\ \hline \end{array}\\ \small \begin{array}{|l|} \hline O=\\ \hline 2 m^2 \\ \hline 200 dm^2 \\ \hline 2\cdot 10^{4} cm^2 \\ \hline 2\cdot 10^{6} mm^2 \\ \hline 0,02 a \\ \hline 0,0002 ha \\ \hline 2\cdot 10^{-6} km^2 \\ \hline \end{array}\\ \small \begin{array}{|l|} \hline a=\\ \hline -1,44 m \\ \hline -14,4 dm \\ \hline -144 cm \\ \hline -1,44\cdot 10^{3} mm \\ \hline -1,44\cdot 10^{6} \mu m \\ \hline -0,00144 km \\ \hline \end{array}\\$